OPPORTUNITIES AND CHALLENGES IN THE IMPLEMENTATION OF TEN REVITALIZATION STRATEGIES OF VOCATIONAL SCHOOLS IN INDONESIA: SCHOOL PRINCIPALS’ VOICES - Ahmad Kailani; Dina Rafidiyah (International Journal of Educational Best Practices, 2020)
The alumni of Vocational Schools (VS) have contributed to the increasing number of unemployment recently. At the onset, the main objective of vocational education is to produce ready to work alumni. However,  the more the schools produce alumni, the higher the number of jobless people in this country. To tackle the issue,  the government launch revitalization programs for VS’s across Indonesia. The implementation of the program is intended to cut down the number of unemployment and poverty. To explore the implementation of the program within a vocational context, this study was undertaken to look at the understanding of VS principals about the revitalization programs as well as the ten core strategies of the program. Besides, the study was also conducted to explore the problems faced the principals and their expectations of the revitalization program. A qualitative phenomenology study using in-depth interviews were conducted to garner the data from nine school principals of private and public VS’s in South Kalimantan Province, Indonesia. The findings indicate that the improvement of the competency of certified teachers is essential. Furthermore, the availability of business and industrial based (DUDI) facilities and learning resources, as well as the availability of professional development training through a link and match programs, are also important. On the other hand, the establishment of Management Information System (SIM) based on School Automation System (SAS), industry-based curriculum, teaching factory, tutorial video, local wisdom, and the role of VS as the triggers of the local economy needs more socialization by the government.